Membangun Literasi Digital Berbasis Pancasila untuk Mewujudkan Masyarakat Cerdas dan Berintegritas dalam Mencegah Penyebaran Informasi Hoax - Stivani Astri Kusumaningrum; Nadia Hanifa; Refa Fadola Fala Resi; Intan Dewi Anitasari; Agdilla Syahba Arzetinindya (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
The proliferation of hoaxs in the digital era poses a significant threat to Indonesia’s social cohesion and national unity. This study explores Pancasila-based digital literacy as a culturally rooted solution to combat misinformation. Employing a literature review method, the research analyzes academic sources from Google Scholar, Sinta, and ScienceDirect, focusing. on the integration of Pancasila values into digital literacy frameworks. Thematic analysis identified three key areas: conceptual foundations, implementation strategies, and challenges. Findings reveal that Pancasila serves as an ethical framework, guiding critical information assessment through principles like humanity, unity, and social justice. Effective strategies include social media campaigns, community collaborations, and curriculum integration. The study concludes that combining technical digital skills with Pancasila values fosters responsible digital citizenship, offering a sustainable approach to counter hoaxes while strengthening national resilience.